Cameroon : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2020)
Since the approval of the first Rapid Credit Facility (RCF-1) request on May 4, 2020 (IMF Country Report No 20/185), weaker external demand in major trading partners (China and Europe) and a more pronounced impact of containment measures to slow the rising number of COVID-19 cases, have further deteriorated growth prospects and worsened Cameroon's external and fiscal positions. Given limited fiscal buffers and urgent balance of payments needs due to the pandemic, the authorities allowed the current ECF arrangement expire at end-September, reiterated their interest on a successor arrangement, and in the meantime requested financial assistance under the 'exogenous shocks window' of the RCF equivalent to 40 percent of quota (SDR 110.4 million). This additional request will bring the total disbursement under the RCF to 100 percent of quota in 2020.